HUBUNGAN FAKTOR PENYULIT PREOPER HUBUNGAN FAKTOR PENYULIT PREOPERASI TERHADAP KETAJAMAN PENGLIHATAN POSTOPERASI DENGAN METODE SICS PADA PASIEN KATARAK - Nurhayati Nurhayati; Zaenal Arifin; Hapipah Hapipah; Maelina Ariyanti (Jurnal Ilmiah Keperawatan, 2020)
World Health Organization (WHO) in 2013 showed that cataracts are the main cause of blindness in the world around 42 %. The cataract or turbidity of the eye lenses is the most common cause of decreased visual acuity in Indonesia. Preoperative complications can interfere with the smooth operation so that the best visual acuity results are difficult to achieve. This study aims to determine the relationship between preoperative complications and visual acuity after cataract surgery at the Community Eye Health Center (BKMM) NTB in 2018. This type of research is an analytic observational case control research approach. The population in this study were all patients who have performed cataract surgery using the Small Incision Cataract Surgery (SICS) method and performed Intra Ocular Lens (IOL). The number of samples in this study were 70 people with sample techniques using consecutive sampling. This research was conducted at BKMM NTB on February 13 - March 13 2018. The data collection tool in this study was the observation sheet. Data analysis using Chi Square test. The results of the study obtained p-value = 0.0005 (a = 0.05) so Ho is rejected. It can be concluded that there is a significant relationship the pre-operative factors of the operation on the post-operative vision acuity with the SICS method at Community Eye Health Center (BKMM) NTB in 2018. Recommendations that can be given are cross-program collaboration with health service agencies in order to conduct health promotion and improve human resources